Turbulence and diapycnal mixing in Drake Passage - St. Laurent, Louis C.; Naveira Garabato, Alberto C.; Ledwell, James R.; Thurnherr, Andreas M.; Toole, John M.; Watson, Andrew J. (Journal of Physical Oceanography, 2012)
Author Posting. © American Meteorological Society, 2012. This article is posted here by permission of American Meteorological Society for personal use, not for redistribution. The definitive version was published in Journal of Physical Oceanography 42 (2012): 2143–2152, doi:10.1175/JPO-D-12-027.1. Direct measurements of turbulence levels in the Drake Passage region of the Southern Ocean show a marked enhancement over the Phoenix Ridge. At this site, the Antarctic Circumpolar Current (ACC) is constricted in its flow between the southern tip of South America and the northern tip of the Antarctic Peninsula. Observed turbulent kinetic energy dissipation rates are enhanced in the regions corresponding to the ACC frontal zones where strong flow reaches the bottom. In these areas, turbulent dissipation levels reach 10−8 W kg−1 at abyssal and middepths. The mixing enhancement in the frontal regions is sufficient to elevate the diapycnal turbulent diffusivity acting in the deep water above the axis of the ridge to 1 × 10−4 m2 s−1. This level is an order of magnitude larger than the mixing levels observed upstream in the ACC above smoother bathymetry. Outside of the frontal regions, dissipation rates are O(10−10) W kg−1, comparable to the background levels of turbulence found throughout most mid- and low-latitude regions of the global ocean. This work was supported by the U.S. National Science Foundation and by the Natural Environment Research Council of the United Kingdom. 2013-06-01